When thermal risk indices work and when they don’t: A case study of two maize insect pests - Komi Mensah Agboka; Frank Thomas Ndjomatchoua; Luca Rossini; Ritter A. Guimapi; Elfatih M. Abdel-Rahman (MethodsX)
The biological life cycle of terrestrial arthropods, using temperature as the primary driving factor has a large interest for insect pests in agriculture, forestry, urban ecosystems, as constitutes the basics for the development of mathematical models for decision making. A recent study proposed a physiologically-based risk index (RI) which finds large applications in the definition of risk maps; however, further case studies are needed to better explore its strengths and limitations. This study aims to extend this knowledge by presenting an application of the RI on two economically significant pests: the fall armyworm Spodoptera frugiperda and the stem borer Busseola fusca, major treats for maize production. • While the case of S. frugiperda follows the theoretical expectations, providing values RI>1 for temperature ranges typical of the regions of its confirmed persistence, the model fails for B. fusca, as RI<1 for weather conditions where field presence and damage are well-documented. • Accordingly, we trace the breakdown to limiting model assumptions, particularly temperature-only drivers, linear cause-and-effect biodemographic parameters, omission of seasonal dynamics, and reliance on laboratory parameters. • This dual-case contrast highlights both the potential and limitations of RI and calls for refinements that include a broader ecological realism and data availability.